﻿Molecular docking and dynamic simulations study for repurposing of multitarget coumarins against SARS-CoV-2 main protease, papain-like protease and RNA-dependent RNA polymerase - Mai E. Shoman; Amer Ali Abd El-Hafeez; Moteb Khobrani; Abdullah A. Assiri; Sultan S. Al Thagfan; Eman M. Othman; Ahmed R. N. Ibrahim (Pensoft Publishers, 2022)
Proteases and RNA-Dependent RNA polymerase, major enzymes which are essential targets involved in the life and replication of SARS-CoV-2. This study aims at in silico examination of the potential ability of coumarins and their derivatives to inhibit the replication of SARS-Cov-2 through multiple targets, including the main protease, papain-like protease and RNA-Dependent RNA polymerase. Several coumarins as biologically active compounds were studied, including coumarin antibiotics and some naturally reported antiviral coumarins. Aminocoumarin antibiotics, especially coumermycin, showed a high potential to bind to the enzymes' active site, causing possible inhibition and termination of viral life. They demonstrate the ability to bind to residues essential for triggering the crucial cascades within the viral cell. Molecular dynamics simulations for 50 ns supported these data pointing out the formation of rigid, stable Coumermycin/enzyme complexes. These findings strongly suggest the possible use of Coumermycin, Clorobiocin or Novobiocin in the fight against COVID-19, but biological evidence is still required to support such suggestions.